Evolution of pore structure during microwave freeze-drying of Chinese yam - Duan, Liuliu; Duan, Xu; Ren, Guangyue (International Journal of Agricultural and Biological Engineering, 2018)
In order to reduce the energy consumption of freeze drying (FD), microwave freeze drying (MFD) can be used to dry Chinese yam. Porosity is a critical factor influencing transport mechanism, and can be considered as an important index to reflect the changes of structure of MFD foods. In this study, the changes of pore structure during the process of MFD Chinese yam were investigated by SEM and mercury porosimetry. The results showed that some closed pores could transform to open pores in drying process, and the open porosity showed a rising trend throughout the drying process. The pore size distribution range was about 10 nm to 106 nm throughout the drying process. In the early stage of drying, the pore size was mainly in the range of 10-104 nm, and then the pore size and the number of pores reduced. In the middle and late drying stages, the size of large pores increased again.Keywords: microstructure, microwave freeze drying, porosityDOI: 10.25165/j.ijabe.20181106.4250Citation: Duan L L, Duan X, Ren G Y. Evolution of pore structure during microwave freeze-drying of Chinese yam. Int J Agric & Biol Eng, 2018; 11(6): 208–212.